the growth and productivity - Pratiwi, Anak Agung Ayu Putri Indra; Arisoesilaningsih, Endang (Biotropika: Journal of Tropical Biology, 2014)
This study aimed to determine the growth and productivity of several local hydromacrophytes such as Acorus calamus L.,